Importance of leadership in architectural education - Kasapoğlu, Esin (My University, 2013)
People are social living being that live in groups. Leadership is needed for collecting people around a group and reaching both personal and common objectives. Leadership has always been a topic of interest in the field of organizational behavior. Although leadership is frequently observed, it is not really very well understood. Differing situations of leadership and different kinds of leaders have led to numerous definitions of leadership, some based on leader behaviors, some on leader characteristics, and others on outcomes or end results. One of the more useful definitions of leadership is the process of influencing others to facilitate the attainment of organizationally relevant goals. Architects require a high degree of personal skills and social competence to lead. Whether it is the partners involved or the tradesperson who will work on implementing the building project, the architect will come into contact with a large number of professional partners in the course of the project. When a large number of people are working on a project, a high level of successful teamwork is required. A high level of social competence is required to work in a team and to be able to deal with all kinds of people. Architects are leaders of both the architectural design team and generally the design team. As the leader of both groups, the relationship between the leader architect and the groups is directly related to the project’s success. Coordinating design projects, structural projects and installation projects is the responsibility of the architect as the team leader. The National Architectural Accrediting Board, Inc. (NAAB) establishes student performance criteria to help substantially equivalent degree programs prepare students for the profession while encouraging educational practices suited to the individual degree program. The 2012 Conditions for Substantial Equivalency apply to all programs seeking continued substantial equivalency, candidacy, continuation of candidacy, or initial substantial equivalency beginning April 1, 2012. For the purpose of substantial equivalency, graduating students must demonstrate understanding or ability as defined below in the Student Performance Criteria (SPC): Realm A: Critical Thinking and Representation, Realm B: Integrated Building Practices, Technical Skills, and Knowledge, Realm C: Leadership and Practice There are 9 subtitles under the title of Realm C: Leadership and Practice. One of these subtitles is C. 6 Leadership. It is defined as understanding of the techniques and skills architects use to work collaboratively in the building design and construction process and on environmental, social, and aesthetic issues in their communities. The purpose of this study is emphasizing the importance of gaining architect candidates’ leadership qualities during their education. This study will be based on a research investigating program curricular framework of twenty architectural schools from different parts of the world. The research will comprise an investigation over leadership training courses in architectural programs. If there are any courses through leadership education or any other courses aiming to gain architect candidates’ leadership qualities will be investigated. At the end of the study, there will be a discussion through a new model of program curricular framework.
Keywords: Leadership; Architect; Architecture; Architectural Education